2018
DOI: 10.1016/j.hpb.2018.02.636
|View full text |Cite
|
Sign up to set email alerts
|

Insight on ALPPS – Associating Liver Partition and Portal Vein Ligation for Staged Hepatectomy – mechanisms: activation of mTOR pathway

Abstract: Rapid liver regeneration with ALPPS might be associated with hepatocyte proliferation induced by mTOR pathway activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
(43 reference statements)
0
8
0
2
Order By: Relevance
“…The mechanism by which ALPPS promotes liver regeneration is not yet clear. Previous studies have indicated that it may be associated with changes in hepatic blood flow caused by the portal veins of the ligated hepatic lobe (41), the inflammatory response and stress response caused by disassociation of the liver or changes in proliferation-associated factors (17,42).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which ALPPS promotes liver regeneration is not yet clear. Previous studies have indicated that it may be associated with changes in hepatic blood flow caused by the portal veins of the ligated hepatic lobe (41), the inflammatory response and stress response caused by disassociation of the liver or changes in proliferation-associated factors (17,42).…”
Section: Discussionmentioning
confidence: 99%
“…Forty-one patients with NET requiring the ALPPS approach have been published so far (http://fp.amegroups. cn/cms/ef5b8bf3a11b76b474fa9762e46828a7/hbsn-20-355-3.docx) (22,27,28,(32)(33)(34)(35)(36)(37)(38)(39). In all the patients but one, the treatment was done for hepatic NET metastases.…”
Section: Alpps Cases In Net Patientsmentioning
confidence: 99%
“…Our analysis showed that pretreatment with chemotherapy and liver parenchyma damage significantly reduce hypertrophy. Nevertheless, further studies are needed, particularly regarding liver regeneration within the setting of ALPPS after chemotherapy [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%